Odour‐causing compounds in air samples: Gas–liquid partition coefficients and determination using solid‐phase microextraction and GC with mass spectrometric detection. Issue 6 (19th February 2013) - Godayol, Anna; Alonso, Mònica; Sanchez, Juan M.; Anticó, Enriqueta
<x xml:space="preserve">Abstract</x> A quantification method based on solid‐phase microextraction followed by GC coupled to MS was developed for the determination of gas–liquid partition coefficients and for the air monitoring of a group of odour‐causing compounds that had previously been found in wastewater samples including dimethyl disulphide, phenol, indole, skatole, octanal, nonanal, benzothiazole and some terpenes. Using a divinylbenzene/carboxen/polydimethylsiloxane fibre, adsorption kinetics have been studied to define an extraction time that would avoid coating saturation. It was found that for an extraction time of 10 min, external calibration could be performed in the range of 0.4–100 μg/m3, with detection limits between 0.1 and 20 μg/m3. Inter‐day precision of the developed method was evaluated (n = 5) and RSD values between 12 and 24% were obtained for all compounds. The proposed method has been applied to the analysis of air samples surrounding a wastewater treatment plant in Catalonia (Spain). In all air samples evaluated, dimethyl disulphide, limonene and phenol were detected, and the first two were the compounds that showed the highest partition coefficients.